Road safety level : a case study of major road linked Terengganu and Kuantan town - Nurul Ain, Che Zakaria (2010)
It is a dual carriageway road which experienced a heavy traffic movement and consequently has recorded a high numbers of accident from year to year. This study is intended to explore statistic of accident rate for Jalan Beserah - Kuantan and Bypass - Kuantan which is one of the gateways to Kuantan City from Terengganu Border. The main data of this study which is the accident data were gathered from the Royal Police Malaysia, Traffic Units who has a state wide database on the accident occurred at all road in Pahang. The data was taken in a period of 4 years from year 2006 to year 2009 to make sure that the data depicted the real situation of this road. After all data was successfully collected, Biviarite Correlation Analysis from the Statistical Package for Social Science (SPSS) was used to determine the correlation. From the findings, the trend of . the accident is the highest accident occurrence is at a rural area where people tend to neglect safety and lack of proper road safety measures. The road accidents increase gradually from year 2006 to 2008 and it decreasing in year 2009. In conclusion, data storage on road accidents must be completed and updated because it is very important when discussing an accidents problem in Malaysia.